This is the equation of an ellipse.
I assume you want it in standard form
complete the square
x^2 + 4x + 4 + 9(y^2 - 4y + 4) = -4 + 4 + 36
(x+2)^2 + 9(y-2)^2 = 36
divide both sides by 36
(x+2)^2 /36 + (y-2)^2 /4 = 1
Answer this Question
Algebra - -3y^3+24y^2-36y
college algebra - 8x+9y=33 x-36y=-330 elimination
Algebra 2 - Factor completely: (0.36y^2-0.0001)
algebra - Factor the expression 25x^2-60xy+36y^2 into a product of binomials.
algebra - 84y^3 ______ 36y^4 Reduce?? See my comment to your first post.
intermediate algebra - Factor the expression 25x^2- 60xy+36y^2 into a product of...
ALGEBRA - 1, Factor each expression x^2 - 10x - 24 A. (x + 4)(x - 6) B. (x + 6)(...
Algebra - Would this be correct? Factpr completley: y^3-12y^2+36y y(y^2-12y+36) ...
drwls:precalc - 4x^2-9y^2-40x+36y+100=0 I still end up with the wrong answer. I ...
precalculus - x=36y-3y^2-64 what is the vertex of this equation?